Strategi komunikasi pemasaran UMKM Kali Jegles berbasis digital - Rudi Santoso; Achmad Yanu Alif Fianto; Dhika Yuan Yurisma (Universitas Pendidikan Indonesia (UPI), 2021)
The application of a digital-based Marketing Communication Strategy is one strategy to help MSMEs rise from the pandemic. This activity takes place in 3 initial stages starting from identification to the initial introduction of digital marketing tools. The three stages include problem identification and observation, MSME motivation, and Digital Marketing Strategy. The result of this activity is an initial design or social media-based digital marketing design. The object of the activity is the Kali Jegles Stren MSME group which is domiciled in Kediri and operates in the culinary and craft sectors. The MSME group really feels the impact of the COVID-19 pandemic, but that does not mean MSMEs must continue to suffer losses even to the point of going out of business. The results of the initial design of this activity can be continued back into a larger activity scheme by providing knowledge and mastery related to Pricing Strategy, Selling Strategy, Retaining Customers, and Profit Taking Strategy.